Plasma cell survival in the absence of B cell memory. Issue 1 (December 2017) - Hammarlund, Erika; Thomas, Archana; Amanna, Ian; Holden, Lindsay; Slayden, Ov; Park, Byung; Gao, Lina; Slifka, Mark
Abstract Pre-existing serum antibodies play an important role in vaccine-mediated protection against infection but the underlying mechanisms of immune memory are unclear. Clinical studies indicate that antigen-specific antibody responses can be maintained for many years, leading to theories that reactivation/differentiation of memory B cells into plasma cells is required to sustain long-term antibody production. Here, we present a decade-long study in which we demonstrate site-specific survival of bone marrow-derived plasma cells and durable antibody responses to multiple virus and vaccine antigens in rhesus macaques for years after sustained memory B cell depletion. Moreover, BrdU+ cells with plasma cell morphology can be detected for 10 years after vaccination/BrdU administration, indicating that plasma cells may persist for a prolonged period of time in the absence of cell division. On the basis of these results, long-lived plasma cells represent a key cell population responsible for long-term antibody production and serological memory. The long-term maintenance of antibody-secreting plasma cells and the requirement for memory B cells are unclear. Here, the authors show that plasma cells and the antibodies secreted are long-lived and maintained over a decade in the absence of memory B cells in non-human primates.